Quantized Output Feedback Control for Stochastic Semi-Markov Jump Systems With Unreliable Links - Shen, Hao; Dai, Mingcheng; Yan, Huaicheng; Park, Ju H. (IEEE transactions on circuits and systems. II, Express briefs, 2018)
This brief is concerned with the problem of quantized output feedback (OF) control for semi-Markov jump systems subject to unreliable links. The jump among the operation modes is subject to the semi-Markov process, where the transition probabilities depend not only on the next system mode but the sojourn time at current mode as well. The communication link is considered to be unreliable, in which the packet dropouts described by a stochastic Bernoulli parameter and signal quantization are taken into account simultaneously. The purpose is to synthesize an OF controller, which ensures that the closed-loop system is mean-square σ -error stable. Some sojourn time-dependent criteria are established for the realizability of admissible OF controller. With the help of those criteria, the controller gains could be obtained by finding a solution to a convex optimization problem. Finally, both a numerical example and a PWM-driven boost converter are presented to confirm the availability and feasibility of the proposed approach.